TO OVERCOME LANGUAGE DIFFICULTIES FOR THE PRIMARY SCHOOLS - Shabonova Shakhnoza (Лучшие интеллектуальные исследования, 2023)
Abstract: This research investigates language difficulties based on primary school pupils and how to overcome this language barriers. Most children come across with language difficulties (delay or disorder), and these difficulties can present and affect language in different ways. Below are some commonly language problems are described. These might be known by a variety of different names and many children will have a combination of these difficulties. Expressive language disorder – this is a pupil’s ability to express ideas and information. It reflects primary education pupil`s ability to produce language, and their use of vocabulary and grammar.